Ar 3p photoelectron sideband spectra in two-color XUV + NIR laser fields. (19th March 2018) - Minemoto, Shinichirou; Shimada, Hiroyuki; Komatsu, Kazma; Komatsubara, Wataru; Majima, Takuya; Mizuno, Tomoya; Owada, Shigeki; Sakai, Hirofumi; Togashi, Tadashi; Yoshida, Shintaro; Yabashi, Makina; Yagishita, Akira
Abstract: We performed photoelectron spectroscopy using femtosecond XUV pulses from a free-electron laser and femtosecond near-infrared pulses from a synchronized laser, and succeeded in measuring Ar 3 p photoelectron sideband spectra due to the two-color above-threshold ionization. In our calculations of the first-order time-dependent perturbation theoretical model based on the strong field approximation, the photoelectron sideband spectra and their angular distributions are well reproduced by considering the timing jitter between the XUV and the NIR pulses, showing that the timing jitter in our experiments was distributed over the width of 1.0 + 0.4 − 0.2 ps. The present approach can be used as a method to evaluate the timing jitter inevitable in FEL experiments.